1958
DOI: 10.3402/tellusa.v10i1.9220
|View full text |Cite
|
Sign up to set email alerts
|

The Easterly Jet Stream in the Tropics

Abstract: It is shown that in summer an easterly jet stream overlies southern Asia in the high troposphere with core near I$"'.This current is quasi-geostrophic. Below the level of strongest winds temperatures decrease from right to left across the current looking downstream; above the level of strongest wind (150-100 mb) the reverse is true. Distribution of cloudiness and precipitation in the lower monsoon correspond to that noted in association with westerly jet streams in the temperate zone: precipitation downstream … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
76
0
1

Year Published

1976
1976
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 164 publications
(77 citation statements)
references
References 6 publications
0
76
0
1
Order By: Relevance
“…West phase years 1953, 1955, 1957, 1961, 1966, 1969, 1971, 1973, 1975, 1978, 1980, 1985, 1990, 1995, 1997, 1999, 2002, 2006, 2008East phase years 1954, 1956, 1958, 1960, 1962, 1963, 1965, 1968, 1970, 1972, 1974, 1976, 1977, 1979, 1981, 1982, 1984, 1986, 1987, 1989, 1991, 1992, 1994, 1996, 1998, 2000, 2001, 2003, 2005, 2010, 2012 methods, EMD is empirical, intuitive, direct and adaptive (Wu and Huang, 2009). The main idea of EMD is to decompose the data locally into different oscillatory components called IMF.…”
Section: Qbo Phases Yearsmentioning
confidence: 99%
See 2 more Smart Citations
“…West phase years 1953, 1955, 1957, 1961, 1966, 1969, 1971, 1973, 1975, 1978, 1980, 1985, 1990, 1995, 1997, 1999, 2002, 2006, 2008East phase years 1954, 1956, 1958, 1960, 1962, 1963, 1965, 1968, 1970, 1972, 1974, 1976, 1977, 1979, 1981, 1982, 1984, 1986, 1987, 1989, 1991, 1992, 1994, 1996, 1998, 2000, 2001, 2003, 2005, 2010, 2012 methods, EMD is empirical, intuitive, direct and adaptive (Wu and Huang, 2009). The main idea of EMD is to decompose the data locally into different oscillatory components called IMF.…”
Section: Qbo Phases Yearsmentioning
confidence: 99%
“…Different physical mechanisms accountable for the maintenance of the TEJ are found in literature. Koteswaram (1958) and Flohn (1964) related the low level monsoonal flow and rainfall to the variation in intensity of the TEJ. Previous study by Krishnamurti and Bhalme (1976) observed that the cumulus convection results in latent heat release which leads to coupling of the lower level circulation with the upper level circulation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Associated with this, there is an upper level zonal wind maximum in the form of a strong easterly jet with its core at 12°N, i.e., about 13° southward of the primary continental rainbelt along the seasonal monsoon trough over India and 13° north of the maritime ITCZ. This is a strong monsoon component and a prominent large-scale monsoon circulation feature called the tropical easterly jet (TEJ), which is observed only over the Indian longitudes during the summer monsoon season (Koteswaram 1958). A meridional section of zonal wind velocity at 70°E based on ERA-40 is shown in Fig.…”
Section: A Implications: Tropical Easterly Jetmentioning
confidence: 99%
“…ii) The thermal effect as a heat source during the monsoon season, producing a strong thermal anticyclone called the Tibetan High (Yeh, 1950;Murakami, 1958;Koteswaram, 1958;Flohn, 1968;Murakami, 1970) and also to cause the northward shift of the STJ.…”
Section: Introductionmentioning
confidence: 99%